Choice in economic contexts ethnographic and theoretical enquiries - Wood, Donald C. (Research in economic anthropology ;, 2006)
This 25th volume in the Research in Economic Anthropology series contains 12 original papers, nine empirical ethnographic studies and three theoretical essays - all linked by a common concern with economic choice in various social and cultural situations, and authored by researchers in anthropology, economics, and sociology. The ethnographic studies present data collected in Mexico, Paraguay, Columbia, Greece, Morocco, Egypt, Thailand, Taiwan, and Japan. Part I of the volume focuses on work migration, a theme that has received much attention of late. Papers in Part II are concerned with various manifestations of markets and market forces in everyday life, and associated individual, group, or corporate action. Part III consists of studies on economic development, market expansion, and community-wide impacts in Latin America. Finally, papers in Part IV share a common concern with the works of noted economic historian Karl Polanyi, which have influenced researchers in economic anthropology, economics, and sociology in many different ways. The research is global in scope and includes European, Asian, African, and American countries. Special attention is given to Latin American countries and the work of economic historian Karl Polanyi.